(untitled) (JOURNAL OF INNOVATIVE RESEARCH IN MANAGEMENT AND HUMANITIES, 2012)
The study sought to establish the impact of the irregular schooling of 2008- 2010 on teaching and learning in Zimbabwe. The study focused on schools in Mashonaland West Province, randomly selecting three rural secondary schools and conveniently sampling three urban secondary schools from which a sample size of 250 form two and „O‟ Level students was selected. The objectives were to establish the level of school attendance among pupils and teachers, time spent actually learning and school dropout/ repeat cases as well as to investigate the behaviours and attitudes of pupils towards schooling, punctuality, and discipline as a result of teachers‟ strikes. A survey research method was used with questionnaires as data collection tools from students and interviews were held with headmasters. Findings revealed that most of the pupils attended school for less than two months in 2008 with very little time spent actually learning, while a moderate improvement was noted in 2010. Student misbehavior mostly lateness, noisemaking, not doing homework and absenteeism were rampant in the schools and pupils dropped out of school to help fend for their families and the girl child was more affected. There are many students who repeated grades when schools opened in 2009 due to inadequate content coverage in 2008. The study recommends that government puts in place a programme of learning to cater for the many children who dropped out of school and those who did not adequately learn due to the teacher strikes and economic hardships of the time. Parents should be oriented to own schools and be proactive in developing and maintaining the quality of education for their children. The government and responsible authorities should also work towards increasing teachers‟ salaries to levels commensurate with the cost of living in line with their qualifications as recognition of the role they play in the development of human, social and cultural capital. There should be programmes for nurturing teacher professionalism through a proactive teacher training programme in the various teachers‟ colleges and provincial education structures. Families should be encouraged to treat children the same regardless of sex or abilities so as not to lose the gains made in the fight for gender equality.